Genomic Investigation of a Legionellosis Outbreak in a Persistently Colonized Hotel - Sánchez-Busó, Leonor; Guiral, Silvia; Crespi, Sebastián; Moya, Víctor; Camaró, María L.; Olmos, María P.; Adrián, Francisco; Morera, Vicente; González-Morán, Francisco; Vanaclocha, Hermelinda; González-Candelas, Fernando (Frontiers in Microbiology, 2016)
Objectives: A long-lasting legionellosis outbreak was reported between November 2011 and July 2012 in a hotel in Calpe (Spain) affecting 44 patients including 6 deaths. Intensive epidemiological and microbiological investigations were performed in order to detect the reservoirs. Methods: Clinical and environmental samples were tested for the presence and genetic characterization of Legionella pneumophila. Six of the isolates were subjected to whole-genome sequencing. Results: Sequencing of 14 clinical and 260 environmental samples revealed sequence type (ST) 23 as the main responsible strain for the infections. This ST was found in the spa pool, from where it spread to other hotel public spaces, explaining the ST23 clinical cases, including guests who had not visited the spa. Uncultured clinical specimens showed profiles compatible with ST23, ST578 and mixed patterns. Profiles compatible with ST578 were obtained by direct sequencing from biofilm samples collected from the domestic water system, which provided evidence for the source of infection for non ST23 patients. Whole genome data from five ST23 strains and the identification of different STs and Legionella species showed that different hotel premises were likely colonized since the hotel opening thus explaining how different patients had been infected by distinct STs. Conclusions: Both epidemiological and molecular data are essential in the investigation of legionellosis outbreaks. Whole-genome sequencing data revealed significant intra-ST variability and allowed to make further inference on the short-term evolution of a local colonization of L. pneumophila.